Input Data for Forensic Construction and Technical Expertise of Destroyed Buildings - A. A. Revunov (Теория и практика судебной экспертизы, 2020)
One of the pressing issues of forensic activity is the absence of an approved list of the necessary and sufficient documentation to conduct a full and comprehensive study for every type and kind of forensic examination, including construction forensics. This makes the tasks put before an expert more challenging, expands the duration of the examination, and sometimes it even leads to the additional and re-examinations. The resolution of this problem would make the work easier for investigators and experts streamlining their activity at the early stages of investigations. The author identifies the types of input data for forensic construction and technical examinations of destroyed buildings. The article provides a list of documentations regulating the research process in cases of building collapse; limits for the use of equipment and tools are also covered.